1998
DOI: 10.1111/j.1349-7006.1998.tb00571.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Population Density and Cancer Mortality in Taiwan

Abstract: Many investigators have examined urbanization gradients in cancer rates. The purpose of this report was to identify urban-rural trends in cancer mortality rates (1982-1991) for municipalities in Taiwan. For this purpose, Taiwan's municipalities were classified as rural, suburban, urban, or metropolitan, using population density as an ordinal indicator of the degree of urbanization. Average annual age-adjusted, site-specific cancer mortality rates were calculated for both sexes within each population density gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 18 publications
1
25
0
Order By: Relevance
“…No geographic variation has been reported in surveillance [94] or survival following radical prostatectomy [95]. Urbanization has been associated with higher prostate cancer mortality [96].…”
Section: Geographymentioning
confidence: 99%
“…No geographic variation has been reported in surveillance [94] or survival following radical prostatectomy [95]. Urbanization has been associated with higher prostate cancer mortality [96].…”
Section: Geographymentioning
confidence: 99%
“…We matched patients with RAS to those without RAS at a ratio of 1:1 through frequency matching. The potential cancer risk‐confounding factors of age,90 sex,91, 92 monthly insured income,93, 94 geographical region,95 and urbanization level96 were considered and matched (Table 1). As listed in Table 1, all P values were near 1, thereby demonstrating that our matching results were satisfactory and the confounding factors were controlled effectively 89.…”
Section: Discussionmentioning
confidence: 99%
“…In general, breast cancer mortality had been considerably higher in urban populations than non-urban ones (Blot et al, 1977;Goldsmith, 1980;Greenberg, 1983;Muir et al, 1987;Kelesy and Berkowitz, 1988;Yang and Hsieh, 1998). The only "urban factor" consistently mentioned in the literature is air pollution, suggesting that residing in an urban area is a reliable surrogate for increased air pollution exposure (Greenberg, 1983).…”
Section: Resultsmentioning
confidence: 99%
“…It was found that mortality attributed to cancer was associated with urbanization gradients (Yang and Hsieh, 1998;Reynolds et al, 2004a;Hall et al, 2005). In this study, an urbanization index (Tzeng and Wu, 1986) was used to adjust for possible confounding resulting from different urbanizational levels among the municipalities.…”
Section: Socioeconomic Factorsmentioning
confidence: 99%